A possible founder mutation in FZD6 gene in a Turkish family with autosomal recessive nail dysplasia - Ceren Saygı; Yasemin Alanay; Uğur Sezerman; Aslı Yenenler; Nesrin Özören (BMC, 2019)
Abstract Background Autosomal recessive nail dysplasia is characterized by thick and hard nails with a very slow growth on the hands and feet. Mutations in FZD6 gene were found to be associated with autosomal recessive nail dysplasia in 2011. Presently, only seven mutations have been reported in FZD6 gene; five mutations are clustered in the C-terminus, one is at the seventh transmembrane domain, and another is at the very beginning of third extracellular loop. Methods Whole exome sequencing (WES) was applied to the index case, her one affected sister and her healthy consanguineous parents. The mutation was verified via Sanger sequencing. Molecular dynamics simulations of the predicted structures of native and mutant proteins were compared to gain insight into the pathogenicity mechanism of the mutation. Results Here, we report a homozygous 8 bp deletion mutation, p.Gly559Aspfs*16; c.1676_1683delGAACCAGC, in FZD6 gene which causes a frameshift and creates a premature stop codon at position 16 of the new reading frame. Our molecular dynamics calculations predict that the pathogenicity of this frameshift mutation may be caused by the change in entropy of the protein with negative manner, disturbing the C-terminal domain structure, and hence interaction partners of FZD6. Conclusion We identified a homozygous deletion mutation in FZD6 in a consanguineous Turkish family with nail dysplasia. We also provide a molecular mechanism about the effects of the deletion on the protein structure and its possible motions. This study provides a pathogenicity mechanism for this mutation in nail dysplasia for the first time.